Volume 1: Aircraft Engine; Ceramics; Coal, Biomass and Alternative Fuels; Manufacturing, Materials and Metallurgy; Microturbine 2008
DOI: 10.1115/gt2008-51126
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Modeling of Fluid Thermodynamic Properties for Gas Turbine Performance Simulation

Abstract: This paper describes the structure of an advanced fluid thermodynamic model which has been developed for a novel advanced gas turbine simulation environment called PROOSIS. PROOSIS (PRopulsion Object Oriented SImulation Software) is part of the VIVACE-ECP (Value Improvement through a Virtual Aeronautical Collaborative Enterprise - European Cycle Programme) project. The main objective of the paper is to determine a way to achieve an accurate, robust and reliable fluid model. The results obtained demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Nevertheless, fluid tabulations offer several key advantages that have been discussed extensively by Sethi et al [1,25].…”
Section: Fluid Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, fluid tabulations offer several key advantages that have been discussed extensively by Sethi et al [1,25].…”
Section: Fluid Modellingmentioning
confidence: 99%
“…A fluid model for an engine performance code comprises of thermodynamic functions to calculate the unknown local flow properties, at any point (inlet, outlet, or intermediate) of any gas turbine component provided one of a set of twelve compatible input options is satisfied [1]. It should be noted here that previous studies have revealed that the impact of the FAR u parameter can be neglected for gas turbine applications [33].…”
Section: Flow Area Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Π‘ Π΄Ρ€ΡƒΠ³ΠΎΠΉ стороны Π½Π°ΠΊΠΎΠΏΠ»Π΅Π½Π½Ρ‹ΠΉ для Ρ€Π°Π·Π»ΠΈΡ‡Π½Ρ‹Ρ… Π³Π°Π·ΠΎΠ² ΡΠΊΡΠΏΠ΅Ρ€ΠΈΠΌΠ΅Π½Ρ‚Π°Π»ΡŒΠ½Ρ‹ΠΉ ΠΌΠ°Ρ‚Π΅Ρ€ΠΈΠ°Π» зависимости Ρ€ c ΠΎΡ‚ Ρ‚Π΅ΠΌΠΏΠ΅Ρ€Π°Ρ‚ΡƒΡ€Ρ‹ ΠΈ давлСния Π΄Π°Π» Π²ΠΎΠ·ΠΌΠΎΠΆΠ½ΠΎΡΡ‚ΡŒ Ρ€Π°Π±ΠΎΡ‚Ρ‹ с Ρ‚Π°Π±Π»ΠΈΡ†Π°ΠΌΠΈ-массивами [19], интСрполируя Π² ΠΎΠ½Π»Π°ΠΉΠ½ Ρ€Π΅ΠΆΠΈΠΌΠ΅ Π·Π½Π°Ρ‡Π΅Π½ΠΈΠ΅ Ρ€ c ΠΌΠ΅ΠΆΠ΄Ρƒ ΡƒΠ·Π»Π°ΠΌΠΈ ΠΏΠΎ Ρ„ΠΎΡ€ΠΌΡƒΠ»Π΅ Π’Π΅ΠΉΠ»ΠΎΡ€Π° для Ρ„ΡƒΠ½ΠΊΡ†ΠΈΠΈ Π΄Π²ΡƒΡ… ΠΏΠ΅Ρ€Π΅ΠΌΠ΅Π½Π½Ρ‹Ρ… [20]. Π’Π°ΠΊΠΎΠΉ способ опрСдСлСния Ρ€ c f (T; p) ο€½ Ρ‚Ρ€Π΅Π±ΡƒΠ΅Ρ‚ хранСния массивов ΠΈ наличия ΡΠΏΠ΅Ρ†ΠΈΠ°Π»ΡŒΠ½Ρ‹Ρ… ΠΏΠΎΠ΄ΠΏΡ€ΠΎΠ³Ρ€Π°ΠΌΠΌ, Ρ€Π°Π±ΠΎΡ‚Π°ΡŽΡ‰ΠΈΡ… с Π½ΠΈΠΌ, Ρ‡Ρ‚ΠΎ Π½Π΅ всСгда ΡƒΠ΄ΠΎΠ±Π½ΠΎ.…”
Section: Introductionunclassified